The development of zoological research on the solovetskyi biological station (1881–1899) - H. V. Deforzh (History of science and technology, 2017)
The article describes the formation and development of the Solovetskyi station on the White Sea (Russian Empire 1881–1899.), and the activities of the St. Petersburg and Kharkov society of naturalists. It reveals hydrobiological and ecological aspects of the existence of a marine fauna, and hydrological questions. The article also depicts contribution of the outstanding scientist Nikolai Petrovich Wagner (1829–1907), who studied the fauna of the White Sea on the Solovetsky Islands and whose efforts resulted in founding of the first ever biological station in the Russian North (1881).